A painful red eye in an intravenous drug abuser: When not everything is what it seems. Issue 2 (March 2023) - Leuzinger-Dias, Mariana; Godinho, Gonçalo; Lima-Fontes, Mário; Oliveira-Ferreira, Cláudia; Camisa, Elisa; Falcão-Reis, Fernando; Silva, Marta; Figueira, Luís
Introduction: Endogenous endophthalmitis is a rare but devastating ocular infection, resulting from microbial seeding of the eye during bacteremia or fungemia. Among other sources of septicemia, intravenous drug abuse is a significant risk factor, and endogenous endophthalmitis should always be thought of in any patient with a history of injectable drug use, presenting with a painful vision loss and a red inflamed eye. Case Description: We report the case of a 47-year-old male, with a history of injectable drug consumption, who presented to our emergency department complaining of a painful red eye and recent deterioration of visual acuity. After the first clinical hypothesis of endogenous endophthalmitis being considered, the final diagnosis of Human Leukocyte Antigen (HLA) B27-associated acute anterior uveitis was established. Conclusion: Ocular inflammation is one of the most challenging fields in all ophthalmology. Several inflammatory disorders, ranging from a wide variety of infectious and non-infectious conditions, can present themselves with the same clinical signs and symptoms, making their diagnosis extremely defiant.